Organizational Benefits of Human Resource Management Roles in South African State-owned Enterprises - Arvid Muzanenhamo; Bongani Innocent Dlamini (CV. Literasi Indonesia, 2022)
Human Resource Management practitioners have been criticized for lacking business acumen due to the nature of the personnel management concept. There has been a change in Human Resource Management roles from traditional personnel management to Strategic Human Resource Management which seeks to provide organizational competitiveness. This article aims to provide organizational benefits of Human Resource Management to an organization as a result of the Strategic Human Resource Management concept. The strategic nature of Human Resource Management has been revealed in this article as there is evidence of Human Resource Management's contribution to the business success. This paper is a study carried out in a South African State-owned enterprise to identify organizational benefits acquired from Human Resource Management roles. Qualitative research was used in this study, and interviews were administered to obtain data from Human Resource practitioners and departmental supervisors in a state-owned enterprise. 24 participants were purposively selected to provide data for the study. This study revealed that the Human Resource department provides beneficial activities to the organization such as reduction of employee turnover, employee development, employee wellness, and internal communication. The critical discussion provided in this paper would strengthen the body of knowledge on the role of Human Resource Management in improving organizational effectiveness.